Information models of agricultural objects - V. V. Alt; S. N. Olshevsky (Сельскохозяйственные машины и технологии, 2016)
The role of information technologies as interindustry direction of science is presented. The hypothesis of possibility of their uniform information description on the basis of the law on substance circulation in the nature and dialectic interrelation of objects of agricultural production is formulated: earth, plants, animals, machines, environment and society. The interrelation of these resources and its optimality (rationality) is possible on the basis of use of information technologies that in many respects defines efficiency of agrarian production. These postulates unite using a paradigm of information support of technological processes of agricultural production. It is represented by set of objective information (devices, measuring computer systems, information and measuring systems, bases and knowledge data) and subjective one, used at creation of devices, information, expert, and artificial intelligence systems. The authors worked out blocks of information models, calculated and justificated size of the converted word and the size of data stream of the universal block. Their technique of creation of «virtual laboratory» of engine 4Ch10.5/12 (D-144) research with use of the device of data collection of NI PCI-6251 is presented. A special software application is developed to realize interpolating of data of 4-factorial experiment at research of an internal combustion engine.